Inventory Control Planning for Injectable Drugs Using a Continuous Review Model with Product Expiration Considerations: A Case Study of Clinic X - Dian Kristina; Saputra Saputra; Rini Syahfitri; Salsabila Miftah Rezkia; St. Nova Meirizha (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Effective pharmaceutical inventory control is essential for maintaining drug availability while minimizing losses from overstock, stockouts, and product expiration in healthcare facilities. This study examines injectable drug inventory planning at Clinic X using a Continuous Review System within a probabilistic inventory model. Historical demand data for 18 injectable drugs from January to December 2023 were analyzed through demand forecasting, calculation of optimal order quantity, reorder point, safety stock, and maximum inventory level, estimation of expired products, and comparison of total inventory cost before and after implementation of the proposed policy. The results show that the proposed model reduced total inventory cost from IDR 35,853,564 under the existing clinic policy to IDR 23,339,897, yielding savings of IDR 12,513,667, or approximately 35%. The model-based expiration estimate indicated zero expected expired units for all observed injectable drugs under the proposed ordering policy and calculation assumptions. These findings indicate that incorporating product expiration into continuous review inventory planning can support more cost-efficient and responsive drug inventory management in healthcare facilities.